The THE LEGEND OF ANGLING DHARMA AS INSPIRATION IN WORK OF COMIC ART - Munazil, Jamil; Muharrar, Syakir; Mujiyono, Mujiyono (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2022)
The study project that was written, took the theme